Review of Clare Pettitt, Serial Forms: The Unfinished Project of Modernity, 1815-1848 (2020) - James Mussell (Journal of European Periodical Studies, 2023)
Review of Clare Pettitt, Serial Forms: The Unfinished Project of Modernity, 1815-1848 (2020)